Implementasi Aplikasi Administrasi SPP Online Berbasis Web pada Sekolah Menengah Kejuruan - Betantiyo Prayatna; Elsa Charolina L Siantar; Iqbal Pradibya; Errissya Rasywir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
SMK 2 PGRI Kota Jambi is one of the vocational high schools in Kota Jambi that still uses a manual payment system for SPP (Education Development Contribution) without utilizing computerized information systems. Additionally, the school has not yet utilized online SPP payment through a website, despite having computers connected to the internet in the computer lab. The existing school network has not been optimally utilized, as there is no dedicated school website for online SPP payment processing, and information retrieval regarding SPP payments is still done manually, causing difficulties for the administrative staff (Tata Usaha) in finding data. Therefore, this research aims to help resolve the issues by developing a website-based application. The application will be developed using HTML, PHP, and MySQL database programming languages. The Waterfall development method will be employed, and the system modeling tools used include use case diagrams, activity diagrams, class diagrams, and interfaces. The outcome of this research will be a website-based application that can assist in resolving the problems faced by SMK PGRI 2 Kota Jambi in managing their Administrative System